Public or private administration of justice: privatization of prisons - Løvlie, Anders; Guruli, Papuna (Nordisk Tidsskrift for Kriminalvidenskab, 2021)
Abstract This article concerns the privatization of prisons and its consequences for the weakening of the state’s monopoly on punishment. It presents an analytical overview of arguments for and against the privatization of prisons in the light of recent developments in Norway. It concludes that the arguments are complex and interwoven and that they rest on several value judgments and empirical assumptions. Abstract Artikkelen omhandler privatisering av fengsler. Det redegjøres for enkelte generelle trekk ved privatisering av fengsler og fremheves forhold som indikerer at privatisering kan bli aktuelt i Norge. Formålet med artikkelen er å gi en analytisk fremstilling av argumentene for og mot privatisering av fengsler, herunder løfte frem relevante empiriske og verdimessige premisser for spørsmålet om privatisering.